2002
DOI: 10.2135/cropsci2002.1602
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Denitrification Using 15 N‐labeled Fertilizer Applied to Turfgrass

Abstract: because irrigation keeps the soil profile near field capacity and may lead to temporary short-term anoxia Denitrification losses are a possibility from turfgrass because of (Sexstone et al., 1985), while multiple applications of N frequent irrigation, multiple applications of N fertilizers, and an abunfertilizer are common, and large amounts of readily dance of readily decomposable organic C in thatch and verdure. Field decomposable organic C are present in the thatch and experiments were conducted to directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The IPM and organic programs, with proper cultural practices over a longer period, can further reduce the need for synthetic inputs. With regard to the IPM program, we did not apply integrated pest management principles to fertility, especially nitrogen requirements, because nitrogen is always in a constant state of flux in turfgrass (see Horgan et al 2002), and thus, it is difficult to determine the actual amount of nitrogen needed. However, it is possible to assess how much nitrogen is coming from organic matter and microbial biomass, but these were not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The IPM and organic programs, with proper cultural practices over a longer period, can further reduce the need for synthetic inputs. With regard to the IPM program, we did not apply integrated pest management principles to fertility, especially nitrogen requirements, because nitrogen is always in a constant state of flux in turfgrass (see Horgan et al 2002), and thus, it is difficult to determine the actual amount of nitrogen needed. However, it is possible to assess how much nitrogen is coming from organic matter and microbial biomass, but these were not measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With relatively large uncertainties due to spatial variation, the estimated fluxes at the annual scale might have a large possible range, from 0 to 50 %, of total N inputs (Table 1b). Relatively large gaseous N losses through denitrification are expected if N fertilization rates exceed plant needs (Barton et al 1999;Raciti et al 2011b), while long-term fertilization could substantially increase the denitrification potential of soil (Drury et al 1997;Horgan et al 2002b;Šimek et al 2000). Although denitrification may help reduce NO 3 --N leaching from fertilized lawns by converting NO 3 --N to N 2 , high denitrification rates may also increase soil emissions of NO, an air pollutant, and N 2 O, a greenhouse gas.…”
Section: N Losses Through Gaseous and Aqueous Formsmentioning
confidence: 99%
“…Incomplete recovery is traditionally attributed to gaseous loss, especially where leachate is collected. However, in measuring denitrification from Kentucky bluegrass and creeping bentgrass turf, Horgan et al (2002aHorgan et al ( , 2002b found that 15 N deficits were not explained by gaseous losses alone. Total 15 N recoveries in the current study (ranging from ∼50 to 70%) were similar to those of Horgan et al (2002a;57 to 73%), but slightly lower than the ∼60-80% reported by others (Starr and DeRoo, 1981;Miltner et al, 1996;and Engelsjord et al, 2004).…”
Section: N Recoverymentioning
confidence: 99%